EFL In-Service Teacher Training Program in Indonesia: An Analysis of Teachers’ Self-Esteem and Task Perception Development - Laili, Indah Rohmatin; Rochsantiningsih, Dewi; Drajati, Nur Arifah (VELES Voices of English Language Education Society, 2023)
This study explores the impact of the "Guru Penggerak" program (PGP), a key component of Indonesia's "Merdeka Belajar" educational initiative, on the professional development of in-service English as a Foreign Language (EFL) teachers. Focusing on three EFL teachers who participated in PGP, the research examines the development of self-esteem and task perception during the training. Data were collected through semi-structured interviews, narrative frames, and examination of relevant artefacts. Results indicate that PGP effectively aids teachers in understanding and implementing the Merdeka curriculum, enhancing their self-esteem and task perception. Specifically, the study identifies two indicators of improved self-esteem: enhanced understanding of curriculum implementation and engagement in professional learning communities. Similarly, two indicators of enhanced task perception were noted: improved job performance and effective utilization of training modules in teaching. Additionally, the study highlights challenges faced by participants, including shifts in teaching beliefs, increased workload, and perceptions of their role in the program. These insights suggest avenues for refining in-service teacher training programs to better support EFL teachers' professional growth.